Lewis-base adducts of group 11 metal(i) compounds. LVII. crystal structure of bis(2, 6-diacetyl-pyridine)silver(i) perchlorate - Bin, Sidik Silong; Engelhardt, Lutz M.; White, Allan H. (CSIRO Publishing, 1989)
The synthesis and room temperature structural characterization of the title compound [AgL2]+ (ClO4)-, L = 2, 6-diacetylpyridine, are reported. Crystals are orthorhombic, Pcan, a 19.629(7), b 14.603(4) and c 14.469(4) Å, Z = 8; R was 0.050 for 1987 'observed' reflections. The structure contains two independent [AgL2]+ species, the central nitrogen atoms of the quasi-tridentate ligands being opposed in the coordination spheres of the silver atoms. Both have crystallographically imposed 2 symmetry; in one, this is normal to the N-Ag-N line [actual bond angle, 175.6(2)°; Ag-N, 2.316(6), Ag-O, 2.589(7) and 2.522(7) Å], relating the two ligands. In the other, it is coincident; for one ligand Ag-N and Ag-O are 2.285(8) and 2.500(8) Å, while for the other the two values are 2.271(8) and 2.543(7) Å. The silver-nitrogen distances are appreciably longer than the value of 2.166(4) Å found for the [Ag(py)2]+ cation.